A new β-carboline alkaloid from the Streptomyces flocculus CGMCC4.1223 mutant ΔstnK4 - Xiaozheng, Wang; Jing, Wo; Fei, Xu; Xinyue, Xie; Tingting, Huang; Shuangjun, Lin (Tetrahedron, 2023)
The β-carboline alkaloids are a large group of natural and synthetic indole alkaloids with various pharmacological properties. Previously, the gene cluster of streptonigrin biosynthesis (stn) was identified in Streptomyces flocculus CGMCC4.1223, revealing a hypothetical protein (StnK4). In this work, a mutant ΔstnK4 was constructed by genetic manipulation and the mutant produced three β-carboline alkaloids, including two known compounds (oxoproopaline D and oxoproopaline G) and one new compound, namely oxoproopaline H. Structure of the new β-carboline was established by spectroscopic analyses. A biosynthetic pathway for these β-carboline alkaloids was proposed.